Does offshoring shape labor market imperfections? A comparative analysis of Belgian and Dutch firms - Sabien Dobbelaere; Catherine Fuss; Mark Vancauteren (Tinbergen Institute, 2023)
We study the relationship between offshoring and the prevalence and intensity of labor market imperfections at the firm level in Belgium and the Netherlands. Wage markup pricing stemming from workers' monopoly power is more prevalent than wage markdown pricing originating from firms' monopsony power in both countries. Offshoring benefits firms in that imports of final as well as intermediate goods are associated with a higher prevalence and intensity of wage markdowns. The widening effect of offshoring on wage markdowns arises from an increase in productivity that is only imperfectly passed through into an increase in wages. Offshoring is negatively related to the prevalence of wage markups. This also holds for the intensity of wage markups measured by workers' bargaining power in Belgium.
Keywords: F14; F16; J42; J50; 330; Wage markdowns; wage markups; firm-level offshoring